Effect of Marble Dust on the Mechanical, Morphological, and Wear Performance of Basalt Fibre-Reinforced Epoxy Composites for Structural Applications - Rajawat A.S.; Singh S.; Gangil B.; Ranakoti L.; Sharma S.; Asyraf M.R.M.; Razman M.R. (MDPI, 2023)
Basalt; Dust; Epoxy resins; Fibers; Marble; Scanning electron microscopy; Vickers hardness; Wear of materials; Basalt fiber; Fiber reinforced epoxy composites; Marble dust; Mechanical; Mechanical performance; SEM analysis; Sliding wear; Structural applications; Waste marble powders; Wear performance; Reinforcement